(untitled) (Tanzania Medical Journal, 2016)
Background: Rheumatoid factor (RF), an autoantibody, is often present in sera of patients suspected of having arthritis, liver diseases, auto-immune disorders, certain viral and bacteria infections and few healthy individuals. Up till now, factors responsible for the RF presence are not fully understood but the involvement of oxidant-antioxidant imbalance has been suggested. Therefore, this study was carried out to determine the serum levels of selected vitamins and oxidative stress indices in RF-positive patientsMethods: Indices of oxidative stress [malondialdehyde (MDA), total peroxide (TP), total antioxidant potential (TAP)] and vitamins C and E were spectrophotometrically determined in 28 patients with RF-positive sera and 28 age-matched apparently healthy adults whose sera were RF-negative (controls). Thereafter, oxidative stress index (OSI) was appropriately calculated. Presence of RF was determined using latex agglutination method. Student’s t-test was used to compare differences in means while Pearson’s correlation analysis was used to establish the correlation between RFtiter and the biochemical indices.Results: The mean serum levels of TP, MDA and OSI were significantly elevated in RF-positive sera compared with controls. In contrast, the mean serum levels of TAP and vitamin E were significantly lower in RF-positive seracompared with controls.Conclusion: It could be concluded from this study that increased oxidative stress and reduced antioxidant activity in RF-positive sera may contribute to RF related diseases. Thus, monitored co-administration of antioxidants supplement or increased intake of antioxidant containing diets with conventional drugs might be beneficial inpatients with RF related diseases